2022
DOI: 10.1007/s11914-022-00731-0
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA and Diabetic Bone Disease

Abstract: Purpose of Review The incidence of diabetes is increasing worldwide. Diabetes mellitus is characterized by hyperglycemia, which in the long-term damages the function of many organs including the eyes, the vasculature, the nervous system, and the kidneys, thereby imposing an important cause of morbidity for affected individuals. More recently, increased bone fragility was also noted in patients with diabetes. While patients with type 1 diabetes mellitus (T1DM) have low bone mass and a 6-fold risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…From the text mentioned above, it appears that diagnostic tools for identifying patients at risk of fracture are insufficient in both obesity and T2DM. Therefore, it is necessary to specify novel biomarkers that will help determine bone fragility in these diseases [181]. MicroRNAs (miRNAs) are currently receiving considerable attention as biomarkers for various diseases, including obesity, T2DM, and osteoporosis [182].…”
Section: Micrornas As Biomarkers In Obesity T2dm and Osteoporosismentioning
confidence: 99%
“…From the text mentioned above, it appears that diagnostic tools for identifying patients at risk of fracture are insufficient in both obesity and T2DM. Therefore, it is necessary to specify novel biomarkers that will help determine bone fragility in these diseases [181]. MicroRNAs (miRNAs) are currently receiving considerable attention as biomarkers for various diseases, including obesity, T2DM, and osteoporosis [182].…”
Section: Micrornas As Biomarkers In Obesity T2dm and Osteoporosismentioning
confidence: 99%
“…Previous research has indicated the significant impact of miRNAs on T1DM-induced osteoporosis. 12 MicroRNAs, known as post-transcriptional gene regulators, 13 , 14 have been found to be dysregulated in patients with T1DM 15-17 and in patients with osteoporosis, 18 , 19 potentially contributing to impaired bone health. Previous studies have identified an upregulation of miR-144-5p 20 and miR-21-5p, 21 , 22 among other miRNAs, in patients with T1DM.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, previous studies have revealed that the efficacy of BTE scaffolds can be undermined by the harsh microenvironment in bone defect sites, including reactive oxygen species (ROS) accumulation, inflammation storm, bacterial infection [ 10 ], blood supply disruption and tumor recurrence [ 11 ]. Various functional molecules have been consequently induced into BTE scaffolds to address these challenges.…”
Section: Introductionmentioning
confidence: 99%